Acute Toxicity Studies of Bombax cieba Flowers In Mice and Rats (Biological Sciences - PJSIR, 2006)
Aqueous extract of Bombax cieba (red silk cotton tree) flowers exhibited a marked action on central nervous system. The signs and symptoms observed in non-lethal doses through oral and intravenous routes in rats and mice were found to be solely functional and short-lived, while lethal doses imparted pharmacological and toxicological action by affecting physiological mechanism of the body. Furthermore, the magnitude and intensity of the toxic symp- toms exhibited were found to be highly dose dependent. The mortalities that occurred may be due to the direct action on central nervous system. The LD50 as calculated for oral route in rats was 6768.730 mg/kg and for intravenous route in rats and mice were 889.496 mg/kg and 467.84 mg/kg, respectively.